Public earthquake communication in Italy through a multi-source social media platform: The INGVterremoti experience (2010–2022) - Pignone, Maurizio; Amato, Alessandro; Nostro, Concetta; Casarotti, Emanuele; Meletti, Carlo; Quintiliani, Matteo; Lauciani, Valentino (Frontiers in Earth Science, 2022)
Communicating scientific information about earthquakes is an important and delicate issue in countries like Italy, where seismic risk is high. Furthermore, continuous and scientifically sound communication is needed, especially in recent times when social media have amplified the risk of being biased by misinformation, fake news and conspiracy theories. For this reason, we have developed a communication strategy for earthquake science and risk in Italy, mostly based on social media. The INGVterremoti platform was born between 2010 and 2012 with the goal of increasing scientific information released to the public, and also establishing a two-way communication channel between scientists and citizens. In the past 12 years, the INGVterremoti platform has gained trust and popularity, increasing the number of involved people, which amounts today to several hundred thousand. The platform consists of a coordinated suite of social media channels and a blog-magazine, where updates on ongoing earthquake sequences and posts on scientific topics are continuously published. Our end users are mostly citizens, but also authorities and media. Special attention has been given to interactions with the public, especially on our Facebook page, in order to understand their information needs, identify rumors and fake news, particularly in areas affected by seismic sequences, and address the most pressing requests. In this paper we describe the INGVterremoti strategy, the different media that we use, focusing on their strengths and weaknesses. We concentrate on the experience, carried out in the last few years, of the publication of provisional information on ongoing earthquakes, a long-standing issue strongly requested by our followers. The INGVterremoti platform has played a fundamental role in many seismic sequences of the past 12 years in Italy, starting from the Emilia sequence in 2012, to the central Italy one, started with the deadly earthquake of August 24, 2016 and still ongoing. Besides the periods of high attention after strong earthquakes, we used the INGVterremoti social media as a tool for releasing continuous and sound information to the public, and as a way to involve citizens in the communication arena.